ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH KULIAH DI PRODI D-III KEPERAWATAN UNIVERSITAS DARMA AGUNG MEDAN - SUBUR SIMANULLANG (LP2MTBM MAKARIOZ, 2020)
Improving the quality of education is influenced by aspects of the curriculum, aspects of the teaching staff, teaching methodsand facilities. The purpose of this study was to determine the effect of the marketing mix (price, promotion, place, people,process, and service) and the environment on student decisions to choose to study at D-III Nursing Program at Darma AgungUniversity (UDA) Medan. This type of research is descriptive quantitative, namely explaining the influence of the marketingmix and the environment on student decisions to choose to study at the D-III Nursing Program at UDA Medan. This researchwas conducted from June to August 2018. The population in this study were all 240 students of Nursing Program at UDAMedan. The sample was taken 20% of the total population using the Proportionate Stratified Random Sampling technique,with a sample of 48 people. Based on the results of the multiple linear regression test, it was found that the marketing mixvalue with student decisions was p value 0.000. Environment with student decisions of p value 0.000. The conclusion of thisstudy is the marketing mix (price, promotion, place, people, process, and service) and the environment simultaneously andpartially have a highly significant effect on the student's decision to choose to study in the D-III Nursing Program at UDAMedan. It is better if the D-III Nursing Program of UDA Medan maintains and increases greater attention to the marketing mixstrategy and the environment which is able to have a positive influence on student decisions to choose to study in the D-IIINursing Program at UDA Medan.